Measurement Uncertainty of Closed Loop Control System for Water Flow Rate - Prakosa, Jalu A.; Putov, Anton V.; Stotckaia, Anastasiia D. (2019 XXII International Conference on Soft Computing and Measurements (SCM), 2019)
the accuracy of water flow rate measurements is the key point of high quality product development, sustainable service of machine and customer justice on its application. The closed loop control of water flow rate system is built on the basis microcontroller equipment to regulate the flow rate through pump. Hall Effect flow meter sensors are applied as the feedback elements to measure water flow rate. The aim of this research is to investigate the measurement uncertainty of closed loop control system on water flow rate application. The optimal gain signal is obtained by 0.5 which has the smallest measurement uncertainty around 2.1% at point of (444.0±9.2) ml/min. The repeatability is the most significant contribution to source of measurement uncertainty. The close loop control system for water flow rate has the most efficient actuating gain signal to provide the best of measurement accuracy.